The {-gA/Iç} and {-(I/A)ç} Morphemes in Turkish: A Synchronic Approach to Derivation - Özge Can; Demet Kayabaşı (Dilbilim Araştırmaları Dergisi, 2016)
Derivation processes show a high degree of variation from one language to another and in terms of the range of derivation and frequency of use. This variation indicates that derivation is a productive process, which seems to form a continuum rather than a dichotomy between productivity and unproductivity (Uzun, 2006, p. 90). This study started as a result of our observation that a certain base cannot be clearly identified in the following lexemes: BİLGİÇ, ÇALGIÇ and YARGIÇ. In order to eliminate this uncertainty, it is necessary to determine the range and the frequency of the derivations obtained by the {-gA/Iç} and {-(I/A)ç} morphemes. To this end, we examined the range of the derivations based on these morphemes and investigated their degree of productivity with respect to one another. We also aimed to answer the question whether one of the morphemes can be treated as the other's allomorph and discussed the ways in which the base of the problematic lexemes in question can be determined. Our data were the list of lexemes derived by {-gA/Iç} and {-(I/A)ç} listed in the Turkish Dictionary by Dil Derneği (2002). We discussed the data, compared the findings in the literature with the new data we presented, and thus aimed to contribute to the existing literature.